Inactivation of the serine protease HTRA1 inhibits tumor growth by deregulating angiogenesis - Klose, Ralph; Tetzlaff, Fabian; Fischer, Andreas (Oncogene, 2018)
The serine protease HTRA1 is involved in several vascular diseases and its expression is often deregulated in cancer. We aimed at identifying how HTRA1 in the vasculature affects tumor growth. Here we report that silencing of HTRA1 in cultured endothelial cells increased migration rate and tube formation, whereas forced HTRA1 expression impaired sprouting angiogenesis. Mechanistically, endothelial HTRA1 expression enhanced Delta/Notch signaling by reducing the amount of the weak Notch ligand JAG1. HTRA1 physically interacted with JAG1 and cleaved it within the intracellular domain, leading to protein degradation. Expression of a constitutive active Notch1 prevented the hypersprouting phenotype upon silencing of HTRA1. In HtrA1-deficient mice, endothelial Notch signaling was diminished and isolated endothelial cells had increased expression of VEGF receptor-2. Growth of syngeneic tumors was strongly impaired in HtrA1−/− mice. The tumor vasculature was much denser in HtrA1−/− mice and less covered with mural cells. This chaotic and immature vascular network was poorly functional as indicated by large hypoxic tumor areas and low tumor cell proliferation rates. In summary, inhibition of HTRA1 in the tumor stroma impaired tumor progression by deregulating angiogenesis.